Plastic bronchitis in beta thalassemia minor - Makaresh Yadav; Sneha Tirpude; Jyotsna M Joshi (Lung India, 2013)
Plastic bronchitis is a rare pulmonary disorder associated with various conditions like cystic fibrosis, asthma, pulmonary infection and characterized by formation and expectoration of cast which assumes the shape of the bronchial tree. We report a case of a 33-year-old woman with beta thalassemia minor who developed plastic bronchitis.